Influence of Chitosan Concentration on the Properties of Electrospun Methanol-crosslinked Chitosan/PVA Nanofibers - Nurul Aina Munirah Binti Ahmadi; Noor Fauziyah Binti Ishak; Mohd Reusmaazran Bin Yusof (ASEAN Journal of Chemical Engineering, 2025)
Polymers nanofibers are of great interest due to the growing need for advanced materials to be used in biomedical applications. This research seeks to assess how the chitosan (CS) concentration affects the electrospun methanol-crosslinked CS/polyvinyl alcohol (PVA) nanofibers’ characteristics. Polymer solution compositions containing 10%, 20%, and 30% CS were prepared and electrospun into nanofibers and then crosslinked with methanol to increase their stability. The nanofibers formed were characterized by their morphology, wettability, and crystallographic structure. According to the FESEM, the 20% CS had the largest diameter range (180-240 nm), while the smallest diameter range (120-160 nm) was noticed in the 10% CS. Nonetheless, the rats with 20% CS had the fewest beads during electrospinning. The analysis of WCA shows that the nanofibers had good wettability, as they all exhibited 31° as the lowest contact angle for the 20% CS. From the XRD, the nanofibers fabricated with 10% CS exhibited the highest peak intensity, which implies a more crystalline structure than the rest. However, the 20% CS nanofibers had a more amorphous structure, which could be useful in biomedical applications like wound dressing. The study demonstrates that the concentration of chitosan and methanol crosslinking significantly influences the electrospun nanofibers’s morphological, hydrophilic, and structural aspects.